THE ROLE OF BIG DATA AND ARTIFICIAL INTELLIGENCE IN HR PLANNING TO SUPPORT DIGITAL ENTREPRENEURSHIP INNOVATION - Agustian, Kresnawidiansyah; Santoso, Rukun; Sekarini, Ratih Ayu; Zen, Agustian (PT. LITERASI SAINS NUSANTARA, 2024)
In the last decade, the development of information technology has advanced rapidly, with Big Data and Artificial Intelligence (AI) as two major innovations reshaping the landscape of business and management. Big Data, which refers to large and complex datasets that are difficult to process with traditional methods, has become a valuable asset for organizations in planning and managing human resources (HR). This research aims to explore how Big Data and AI can be applied in HR planning to support digital entrepreneurship innovation, as well as to identify the benefits and challenges of implementing these technologies. This study employs a qualitative approach using a literature review method. Data for this research were collected through a systematic literature search on Google Scholar, focusing on articles published between 2018 and 2024. The results of the study indicate that Big Data provides deep insights through complex and detailed data analysis, enabling companies to plan their workforce needs more accurately and responsively to market changes. AI, on the other hand, enhances efficiency by automating HR processes and providing predictive analytics that can support strategic decision-making. Case studies from companies like Walmart, Unilever, and Airbnb demonstrate how the implementation of these technologies can improve HR planning processes and support innovation in digital businesses.